Perancangan Ulang Tata Letak Pabrik Pada UMKM Pengolahan Air Tahu Di UMKM ATS SOYA Menggunakan Metode Systematic Layout Planning (SLP) Dengan Algoritma BLOCPLAN - Iksan Adiasa; Rianti Indah Lestari; Dian Dwi Wahyudi; Selfian Hamdir (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
ATS Soya is a micro, small, and medium enterprise (MSME) located in Makassar that produces healthy soybean milk without preservatives. The main issue faced by the company is the inefficient production facility layout, which causes motion and waiting waste due to unorganized material flow. This study aims to redesign the production layout to improve efficiency and production capacity. The Systematic Layout Planning (SLP) method combined with the BLOCPLAN software was employed to generate optimal layout alternatives. Data were collected through field observation, direct measurement, and interviews with production operators. The analysis covered the production process flow, activity relationships (Activity Relationship Chart/ARC), and comparisons between available and required space. The results show that the proposed layout reduced total material handling distance from 37.1 meters to 28.46 meters (a 23.29% reduction) and decreased total material handling cost (OMH) from IDR 12.781.600 to IDR 7.954.854,14 (a 37.76% improvement). The study concludes that implementing the SLP method with the BLOCPLAN algorithm effectively enhances spatial efficiency, optimizes workflow, and reduces operational costs at ATS Soya. This research is expected to serve as a reference for other MSMEs seeking to improve production layouts using systematic, data-driven design approaches